Pengaruh Kombinasi Pupuk Kandang Ayam dan Pupuk NPK Terhadap Pertumbuhan Tanaman Cabai Merah Besar (Capsicum annuum L.): The Effect of Combination Chicken Manure and NPK Fertilizer on the Growth of Big Red Chili (Capsicum annuum L.) - Meida, Nur Lathifa; Triani, Nova; Dewanti, Felicitas Deru (University of Darussalam Gontor, Ponorogo, East Java Indonesia, 2024)
Big red chili is a vegetable plant that plays an important role for people in Indonesia as one of the kitchen spices and big red chili fruits have a high selling value. Plant growth and production can be influenced by land conditions to support plant growth and development, so there is a need for organic and balanced fertilization activities. This research conducted in Jabaran Hamlet, Pohkecik Village, Dlanggu District, Mojokerto Regency from October 2023 to February 2024. The research design used was a randomized block design (RAK) consisting of two factors with 3 replications. The first factor is the dose of chicken manure which consists of 15 tons/ha; 20 tons/ha; and 25 tons/ha and the second factor, namely the dose of NPK fertilizer consists of 75%; 50%; and 25%. The results of the study showed that the combination of 20 tons/ha of chicken manure and 25% NPK fertilizer had a real effect on plant height parameters and stem diameter, while the combination of 15 tons/ha of chicken manure and 50% NPK fertilizer had a real effect on the number of leaves.